Evaluation of the Oxyrase OxyPlate Anaerobe Incubation System - Wiggs, Lois S. (American Society for Microbiology, 2000)
The Oxyrase OxyPlate anaerobe incubation system was evaluated for its ability to support the growth of clinically significant anaerobic bacteria previously identified by the Anaerobe Reference Laboratory at the Centers for Disease Control and Prevention. The results were compared with those obtained with conventional anaerobe blood agar plates incubated in an anaerobe chamber. We tested 251 anaerobic bacterial strains. Plates were read at 24, 48, and 72 h; growth was scored by a numerical coding system that combines the degree of growth and the colony size. Organisms (number of strains tested) used in this study were Actinomyces (32), Anaerobiospirillum (8), Bacteroides (39), Campylobacter (8), Clostridium (96), Fusobacterium (12), Leptotrichia (8), Mobiluncus (8), Peptostreptococcus (16), and Propionibacterium (24). At 24 h, 101 (40.2%) of the 251 strains tested showed better growth with the anaerobe chamber than with the OxyPlate system, 10 (4.1%) showed better growth with the OxyPlate system, and the remaining 140 (55.8%) showed equal growth with both systems. At 48 h, 173 (68.9%) showed equal growth with both systems, while 78 (31.1%) showed better growth with the anaerobe chamber. At 72 h, 176 (70.1%) showed equal growth with both systems, while 75 (29.9%) showed better growth with the anaerobe chamber. The OxyPlate system performed well for the most commonly isolated anaerobes but was inadequate for some strains. These results indicate that the Oxyrase OxyPlate system was effective in creating an anaerobic atmosphere and supporting the growth of anaerobic bacteria within 72 h. OxyPlates would be a useful addition to the clinical microbiology laboratory lacking resources for traditional anaerobic culturing techniques.